Understanding and acceptance of open, laparoscopic, and robotic surgery among nursing students: implications for educational curricula based on a mixed-methods study - Özkan, Esra; Çankaya, Askeri; Özsoy, Hatice (Springer Nature, 2025)
This study aimed to assess university nursing students’ knowledge and perceptions of open, laparoscopic, and robotic surgery applications. A simultaneous sequential nested quantitative–qualitative hybrid research method design was conducted. The sub-sample for the qualitative phase was conducted with 35 nursing students using the maximum variation sampling strategy with 423 nursing students studying at two universities located in the north and south-east of Türkiye. The data for quantitative were collected using a structured questionnaire comprising two parts created by the researchers in two parts to determine the nursing student's knowledge levels about surgical techniques and to determine the students' sociodemographic characteristics. The qualitative part consisted of six open-ended questions to determine the level of knowledge of open robotic and laparoscopic surgery. Descriptive data were assessed using numbers, percentages, mean, and standard deviation for quantitative analyses. Qualitative data were collected using thematic analysis after data saturation was achieved. It was found that 90.5% of nursing students knew about open surgery, 70.7% knew about laparoscopic surgery, and 62.4% were familiar with robotic surgery. Nursing students' knowledge levels regarding open, laparoscopic, and robotic surgery were 5.26 ± 2.531, 2.498 ± 2.498, and 3.69 ± 2.165, respectively. Themes, derived from semi-structured interviews are “safe, effective and patient-centered surgical care optimization supported by technology and artificial intelligence in robotic surgery”, “safe surgical care supported by technology and innovation that increases patient comfort and clinical success in laparoscopic surgery”, “risks, challenges and training requirements for improving patient safety and quality of care in open surgery” were discussed. It reveals the need for more studies comparing the superiority of surgical methods in a clinical context. Enhancing knowledge of surgical techniques can improve nursing students' readiness for modern surgical practices, promoting safer and more effective. Emphasis on technological surgical methods in nursing education and to increase training on the differences in surgical methods. The content of the study was explained to all nursing students in the inclusion group, and after obtaining consent from the nursing students who would participate voluntarily, the study was started with the nursing students who participated voluntarily. © The Author(s) 2025.
Keywords: Knowledge level; Mixed design research; Nursing student perception; Surgical education